A prospective multicentre external validation study of the Liverpool Peritonsillar abscess Score (LPS) with a no‐examination COVID‐19 modification. (20th October 2020) - Selwyn, David; Yang, Ding; Heward, Elliot; Kerai, Ashwin; Thompson, Elinor; Shommakhi, Abulgasem; Faulkner, Scott; Siau, Richard; Walijee, Hussein; Hampton, Tom; Chudek, Dorota; Singhera, Supriya; et al.
Abstract: Objectives: Our primary aim was to validate the Liverpool Peritonsillar abscess Score (LPS) externally in a new patient cohort. Our secondary aim was to modify the LPS in the light of the COVID‐19 pandemic to produce a no‐examination variant for use in this instance. Design: Prospective multicentre external validation study. Setting: Six different secondary care institutions across the United Kingdom. Participants: Patients over 16 years old who were referred to ENT with any uncomplicated sore throat such a tonsillitis or peritonsillar abscess (PTA). Main outcome measures: Sensitivity, specificity, positive predictive value and negative predictive value for both the original LPS model and the modified model for COVID‐19. Results: The LPS model had sensitivity and specificity calculated at 98% and 79%, respectively. The LPS has a high negative predictive value (NPV) of 99%. The positive predictive value (PPV) was slightly lower at 63%. Receiver operating characteristic (ROC) curve, including the area under the curve (AUROC), was 0.888 which indicates very good accuracy. Conclusions: External validation of the LPS against an independent geographically diverse population yields high NPV. This may support non‐specialist colleagues who may have concerns about mis‐diagnosing a PTA. The COVID‐19 modification of the LPS has a similar NPV, which may be of use where routine oral examination is to be avoided during the COVID‐19 pandemic.